Effective Used of Oncom Tofu By-Product as a Broiler Chicken Feedstuff - Mahfudz, LD (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2006)
A research was conducted to know affectivity ofÂ âoncomâ of tofu by-product as a broiler chicken feedstuff, was done at Poultry Science Laboratory, Faculty of Animal Husbandry, Diponegoro University Semarang, from September until October 2002. Sixty broiler chick strain Arbor Acres at 1 week old, unsex with initial body weidht 120.08Â±15.58 g was used. Homogeneity test of material used Barlet Test consider of Sudjana (1996). The chicks was postal house litter system with long and wide 10 x 6 m2, open walls and roof from âgentingâ. The house was divided on 20 pen with bamboo stick by 1 x 0.75 x 0.75 m3 per pen. House was comleted by feeder and waterer, brooder and scale triple-beam âO Haustâ. Tofu by-product was fermented by âoncomâ yeast consist of Neurospora sp. Experimental feed based on yellow corn, rice polished, soybean, fish meal and mineral mix and tofu by-product. The feed was formulated with same protein and energy (equal protein and equal energy). The feed for first period with 22% protein and 2.900 kcal/kg, will the feed for last period with 20% protein and 3.000 kcal/kg. The treatment are tofu by-product fermentation as follow : T0, T1, T2 and T3 are 0, 10, 15 and 20% respectively. The parameters were feed consumption, body weight gain, feed conversion ratio, last body weight and carcass percentage. The Completely Randomized Design was used as Experiment design, consist of 4 treatment with 5 replication each, and every experimental unit consist of 3 birds. The data was analyzed by Analysis of Variace (ANOVA) using F-test to know effect of treatment. If there is significantly affected by treatment continued by Multiple Range Test by Duncan (Srigandono, 1989). The experiment result shown that feed consumption, body weight gain, last body weight, carcass weight and carcass percentage significantly (P<0.05) increase, will feed conversion ratio significantly (P<0.05) decrease by tofu by-product fermented with âoncomâ yeast in the ration. The experiment result can be concluded that tofu by-product fermented with âoncomâ yeast was effective as a feedstuff of broiler chicks until 20% in the rations. (Animal Production 8(2): 108-114 (2006)Â Key Words : Tofu by-product fermented by âoncomâ yeast, performance, broiler chick